2017
DOI: 10.1155/2017/5489057
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Homocysteine, Vitamin B12, and Vitamin D Levels on Functional Outcome after First-Ever Ischaemic Stroke

Abstract: We explored the relationship between acute ischaemic stroke (IS) early functional outcome and serum levels of homocysteine, vitamin B12, and D in a noninterventional prospective clinical study. We enrolled 50 patients with first-ever IS and performed laboratory tests and functional assessment at three time points: on admission and three and six months after stroke. Modified Rankin Scale (mRS), NIHSS scale, and Barthel index (BI) scores were assessed in all participants by trained examiner blinded to laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 53 publications
5
39
2
Order By: Relevance
“…At admission, the NIH Stroke Scale (NIHSS) negatively correlated with vitamin D, suggesting that major impairment after stroke correlated with lower levels of vitamin D; adjusting for age and the baseline NIHSS values, a trend in correlations were found between functional outcomes at all timepoints (Barthel index and modified ranking scale) and vitamin D levels. Authors highlighted that they included only surviving patients in the final analysis, so no data about vitamin D levels in dead patients were reported, not allowing a correct evaluation [14]. Moreover, a noteworthy aspect of this study [14] was that vitamin D level increased during the follow-up, whereas no supplementations were administered; authors properly suggested that secondary dietary changes could have contributed to these results which they did not evaluate.…”
Section: Vitamin D and Outcome Of Strokementioning
confidence: 97%
See 4 more Smart Citations
“…At admission, the NIH Stroke Scale (NIHSS) negatively correlated with vitamin D, suggesting that major impairment after stroke correlated with lower levels of vitamin D; adjusting for age and the baseline NIHSS values, a trend in correlations were found between functional outcomes at all timepoints (Barthel index and modified ranking scale) and vitamin D levels. Authors highlighted that they included only surviving patients in the final analysis, so no data about vitamin D levels in dead patients were reported, not allowing a correct evaluation [14]. Moreover, a noteworthy aspect of this study [14] was that vitamin D level increased during the follow-up, whereas no supplementations were administered; authors properly suggested that secondary dietary changes could have contributed to these results which they did not evaluate.…”
Section: Vitamin D and Outcome Of Strokementioning
confidence: 97%
“…Vitamin D and risk of stroke [16,[57][58][59][60][61][62][63][64][65][66] Vitamin D and outcome of stroke [3,[11][12][13][14][15][67][68][69][70][71] Supplementation of Vitamin D and post-stroke recovery [67,72,73] Vitamin D and rehabilitation after stroke [3,[12][13][14][15]74] Appl. Sci.…”
Section: Topic Referencesmentioning
confidence: 99%
See 3 more Smart Citations